Psychometric Properties of the Teachers' Sense of Efficacy Scale for Chinese Special Education Teachers. (April 2021) - Lu, Ming-Hui; Pang, Fei-Fan; Chen, Xiao-Meng; Zou, Yu-Qing; Chen, Jia-Wei; Liang, Di-Chao
Teacher self-efficacy plays an important role in special education; yet, the literature on the measurement of teacher self-efficacy in this field is limited. This study investigated the psychometric properties of the Teachers' Sense of Efficacy Scale with a sample of Chinese special education teachers ( N = 401, 24.19% male). Confirmatory factor analysis indicated that the Chinese special educational version of the Teacher's Sense of Efficacy Scale (CS-TSES), modified from the Asian model by Ruan, J., Nie, Y., Hong, J., Monobe, G., Zheng, G., Kambara, H., & You, S. (2015). Cross-cultural validation of teachers' sense of efficacy scale in three Asian countries. Journal of Psychoeducational Assessment, 33 (8), 769-779, showed an excellent fit. Additionally, correlations were observed between the results of the CS-TSES and both the Multidimensional Scale of Perceived Social Support and the Satisfaction with Life Scale, providing criterion-related validity. In sum, the findings indicated that the TSES is applicable to special education teachers in the Chinese context.